THE METHODS OF FORECASTING OF CHANGES OF MUNICIPAL WASTE PRODUCTION IN CASE OF CITIES - Cheba, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
Waste management is currently one of the most important problems of the functioning of densely populated areas, important in the case of cities. The main problem of waste management is to break a simple correlation between economic growth and the increase in the amount of waste. Forecasting of amount of municipal waste generation on the basis of previously applied methods in the situation of large changes in socio-economic environment turns out to be inaccurate approach. In the literature a wide variety of geographically diverse factors are proposed for this purpose. This paper presents the results of modeling and forecasting of municipal waste generation changes in cities.  In this study, the impact of the various socio-economic factors for the municipal waste production was tested.